Evaluating drug prevention in the European Union: papers arising from the First European Conference on the Evaluation of Drug Prevention held in Lisbon, Portugal, 12 - 14 march 1997 - Baker, Oswin (EMCDDA scientific monograph series, 1998)
Preventing drug use is a universal challenge and identifying approaches that work, and why they work, is a specific objective for drug professionals and evaluators. This monograph focuses on the ideology of prevention in Europe. In particular, it presents arguments for making evaluation a routine and scientifically sound procedure that draws on good practice and proven methodology. The volume includes a broad overview of the history and status of prevention activities and their evaluation in Europe and the US, as well as an introduction to the theoretical foundations of evaluation. Also reviewed are the most commonly encountered evaluation methods, instruments, problems and obstacles and the diversity and complexity of evaluation models. The monograph explores how drug professionals can interest politicians in evaluation and how evaluation can stimulate the allocation of funds.